Analisis Upaya Pencegahan dan Pengendalian Kecelakaan Kerja Pada Sebuah Pabrik Semen di Tuban - A'Izzatul Umamah; Hanifa Maher Denny; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Every organization had risks to face when performing their activities. PT. Semen Indonesia (Persero) Tbk. is a cement company. The company had created accident prevention programs but there was still accident happened to their employees. The study aimed to analyze the efforts of accident prevention and control implemented by PT. Semen Indonesia (Persero) Tbk especially for Tuban I Plant. Method used in this study was qualitative with observational approach. Results showed that management of PT. Semen Indonesia (Persero) Tbk had created the OSH policy and they were reputed to give support in implementing accident prevention. After risks assessed, results obtained that the risks included in low level risks were unorganized equipment, spilled/scattered material, un-ergonomic work station, vibration, boredom, people without interest appearance, excavator usage, electrical usage, transporter truck usage, incompetent personnel, and light radiation, whereas the medium level risks included noise, dust, rotating equipment, high temperature material, gas, and vapor, coal dust, height, scattered/spilled material, and high pressure, and the high level risks included height, noise, and high temperature material. The efforts implemented by OSH section included activity’s impact identification and assessment, safety inspection (unsafe action and condition), safety talk (internal and contractor), recondition and completion of OSH norm sign, OSH training (basic of OSH), managing and supplying the PPE, assessment of 5R implementation, Equipment securing activity ( Log Out and Tag Out), and Plant Equipment Certification. The conclusion of the study was the innovation of preventing and controlling accident needed to be done in work place.